Environmental Kuznets curve for deforestation: evidence using GMM estimation for OECD and non-OECD regions - Joshi P; Beck K (iForest - Biogeosciences and Forestry, 2017)
The depletion of the world’s forests in both tropical and temperate regions threatens to cause considerable environmental problems and hamper future economic development. However, some research has suggested that this deforestation might slow or reverse, exhibiting an Environmental Kuznets Curve (EKC). Yet previous studies investigating such an EKC have found mixed results. We therefore test for a deforestation EKC using an improved dataset from the World Development Indicators and an enhanced econometric technique Arellano-Bover/Blundell-Bond Generalized Method of Moments (GMM) estimator. We compare OECD countries with the non-OECD regions of Latin America, Asia, and Africa to determine how various factors like economic growth, population, trade, urbanization, agricultural land conversion, and cereal yield impact deforestation rates. The results show that the OECD countries have an N-shaped curve whereas only the African region experiences an income-based EKC pattern. Population growth tends to create more deforestation as does conversion to agricultural lands. More trade openness and greater urbanization impact the regions differently, but only the OECD countries have less deforestation due to better cereal yields.